2020
DOI: 10.2147/copd.s240720
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association Between Routine Blood Biomarkers and Clinical Phenotypes and Exacerbations in Chronic Obstructive Pulmonary Disease</p>

Abstract: Introduction: Chronic obstructive pulmonary disease (COPD) is associated with increased lung and systemic inflammation. We aimed to identify associations between easy-to-obtain blood biomarkers and the frequency and severity of exacerbations. Methods: Cross-sectional, multicentre study performed in four centres in Spain, Italy, Bulgaria, and Slovenia. Blood samples were obtained for blood cell count, C-reactive protein (CRP), alpha-1 antitrypsin (AAT) and fibrinogen analysis. The neutrophil/lymphocyte ratio (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
0
19
1
Order By: Relevance
“…15,16 However, the findings on systemic inflammation biomarkers and clinical characteristics of COPD are contradictory. [15][16][17][18][19][20][21] In this way, it is essential to investigate the cell line responsible for synthesizing cytokines that orchestrate inflammation in stable COPD. 22 In addition, exploring correlations not previously investigated between the intracellular inflammatory profile and clinical characteristics and functional status, may contribute to the management of this heterogeneous group of patients, with more promising results and better outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 However, the findings on systemic inflammation biomarkers and clinical characteristics of COPD are contradictory. [15][16][17][18][19][20][21] In this way, it is essential to investigate the cell line responsible for synthesizing cytokines that orchestrate inflammation in stable COPD. 22 In addition, exploring correlations not previously investigated between the intracellular inflammatory profile and clinical characteristics and functional status, may contribute to the management of this heterogeneous group of patients, with more promising results and better outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, PLR was signi cantly associated with an increase in 90day mortality. In addition, there is no difference between NLR, PLR and COPD A-D groups [8]. Relevant studies have shown that the lung is related to the production of platelets [9].…”
Section: Introductionmentioning
confidence: 83%
“…The PLR of patients with stable COPD is signi cantly higher than that of healthy controls, while the PLR level of non-survivors with acute exacerbation of COPD is signi cantly higher, but compared with NLR, PLR is still more effective and simple prognostic indicators [36]. The cross-sectional multi-center study of Alexa et al [8] showed that NLR and PLR are predictors of COPD, but there is no correlation between the two and FEV1, and there is no correlation between the two groups and the GOLD A-D group.…”
Section: Discussionmentioning
confidence: 99%
“…More than 100 allelic variants of the gene coding for the AAT, called Serine Protease Inhibitor-A1 (SERPINA1) exist, whereas many of them are associated with reduced circulating protein levels or altered protein activity (Bornhorst et al, 2007). Individuals with AAT deficiency (AATD), in the presence or in the absence of concomitant factors such as smoke, environmental pollutants, and age, have a very high risk of developing pathologies of the respiratory system, such as pulmonary emphysema and chronic obstructive pulmonary disease (COPD) associated to a progressive damage of lung parenchyma (Nuñez et al, 2020).…”
Section: Alpha-1 Antitrypsin (Aat)mentioning
confidence: 99%
“…Patients affected by COPD frequently present exacerbations, often triggered by bacterial/viral respiratory infections or viruses, which lead to disease progression through an exaggerated inflammatory response, therefore requiring pharmacological treatments (Xiong et al, 2017). COPD exacerbations are characterized by high neutrophil counts, and high levels of C-reactive protein (CRP), as well as inflammatory cytokines including tumor necrosis factor α (TNFα), interleukin-1 (IL1), interleukin-8 (IL8) and IL6 (Bradford et al, 2017;Xiong et al, 2017;Nuñez et al, 2020).…”
Section: Alpha-1 Antitrypsin Therapy In Copdmentioning
confidence: 99%